2015
DOI: 10.1051/0004-6361/201525999
|View full text |Cite
|
Sign up to set email alerts
|

A non-LTE analysis of the hot subdwarf O star BD+28°4211

Abstract: We present the second part of our detailed analysis of the hot subdwarf O (sdO) and spectroscopic standard star BD+28 • 4211, in which we focus on the optical spectrum. This target was selected to revisit the more general question of how reliably the atmospheric parameters of a very hot star can be inferred from optical spectroscopy alone. Given its status as a spectrophotometric standard, spectral data of exceptional quality are available for BD+28 • 4211. In the first part of our study, we determined the abu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…as part of her spectroscopic programmes in recent years (Green et al 2008). A detailed description of the three instrumental set-ups can be found in Latour et al (2015), hence we only describe the main characteristics of the spectra obtained. For each star we have low (∆λ = 8.7 Å) and medium (1.3 Å) resolution spectra taken at the Steward Observatory 2.3 m Bok Telescope on Kitt Peak.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…as part of her spectroscopic programmes in recent years (Green et al 2008). A detailed description of the three instrumental set-ups can be found in Latour et al (2015), hence we only describe the main characteristics of the spectra obtained. For each star we have low (∆λ = 8.7 Å) and medium (1.3 Å) resolution spectra taken at the Steward Observatory 2.3 m Bok Telescope on Kitt Peak.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…This is a known problem when fitting the spectra of CSPNe and other hot stars with pure HHe models only. It has been shown that He II λ 4686 Å is particularly susceptible to metal line blanketing [15,16]. We expect the systematic effects introduced by neglecting metal-line blanketing effects to be of the order of 0.1 dex on log g and 1 kK on T eff [17], but we will include metals in our models for future analysis of this system to overcome this problem.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Indeed, it is thought that analyses based on optical spectroscopy yield systematically cooler temperatures for stars hotter than ∼50 000 K due to the so-called Balmer-line problem (Napiwotzki 1993). For the few cases where both highquality optical and UV data are available and have been exploited for very hot compact evolved stars, the (more reliable) UV spectroscopy yielded temperature estimates over 10 000 K higher than the optical spectra (see Latour et al 2015, for a recent example). We plan to refine the temperatures of the ω Cen variables on the basis of HST-COS spectra in the future, however this is outside of the scope of this study and will be presented in a future publication.…”
Section: The Theoretical Instability Stripmentioning
confidence: 99%